Perencanaan Instalasi Pengolahan Limbah Cair Rumah Sakit Aliyah 3 Kota Kendari - Suwardi, Suwardi; Ndibale, Wa; Kotta, M. Husni; Ilham, Ilham; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
The purpose of this study was to determine the amount of liquid waste discharge at the hospital. Data from the number of hospital patient beds is 54 beds, so the activities taking place in Aliyah Hospital 3 in Kendari city produces a maximum discharge of liquid waste of 3.78/day. The form and design of processing liquid waste which is a rectangle with anaerobic- aerobic bio filter treatment system. Liquid waste processing with anaerobic-aerobic bio filter process consists of several parts namely the oil separator tank, equalization tank, early settling tank, anaerobic bio filter tank, aerobic bio filter tank, final settling tank and equipped with a chlorinated contractor tub. As for the size of each tank, which is like an oil separator tank (0,9 m × 0,5 m × 0,7 m), equalization tank (2,6 m × 1,3 m × 1,1 m), early settling tank (1,6 m × 0,8 m × 0,9 m), anaerobic bio filter tank (2,5 m × 1,3 m × 1,4 m), aerobic bio filter tank (1,8 m × 1 m × 1 m), final settling tank (1,8 m × 0,7 m × 0,7 m) and chlorinated tank (0,6 m × 0,3 m × 0,4 m). This process system was chosen because it is in accordance with the amount of liquid waste treatment system is safe, inexpensive and easy to operate.